Análisis del funcionamiento de los Canales de Comercialización de la Producción Láctea Bovina - Roldán Escudero, Geann Carlo (2017)
The research project was carried out in the Guanujo Parish, Guaranda, Bolívar Province. An analysis was made of the marketing channels for Bovine dairy production in four sectors: Guantug, Moya, Vaquería and Sinche. Faculty of Agricultural Sciences, Natural Resources and Environment, Veterinary and Zootechnical Medicine Career. The objective was to analyze the operation of the marketing channels of the bovine milk production, Identify the actors involved in the dairy marketing, characterize the marketing channels that are presented in the study area and define the marketing segment more acceptable for the Producers in the sector. The methodology proposed through surveys, dialogues, interviews and surveys with a questionnaire of closed questions. Interpretation and analysis based on the application of descriptive statistics and Excel technology package. Among the results obtained shows that the producers produce mestizo cattle, producing from 1 to 10 liters a day in 78.26%, the sanitary management is 82.61% who do, with a manual milking type 86.96%, do not handle properly the registration of 65.22%, the type of feeding by grazing, so they trade in 65.22% in cheese and milk in 34.78%, the sale of milk products to the intermediaries who sell it in jerrycan and the production invests in the farms, food , Education because the greater production of obtainment in winter, they do not have problems of commercialization 69.57%, they have it labor in 93.33% because they work with the families. With regard to intermediaries purchase of 300 - 500 liters per day 62.5%, at a cost of 0.35-0.40 ctvo, being the best price for the quality of milk that intermediaries buy directly from the producer and the sale do it outside of The province in 62.5%, the payment of milk from the intermediary to the producer is weekly in 87.5%.